2012
DOI: 10.3109/17453674.2012.672090
|View full text |Cite
|
Sign up to set email alerts
|

Is MRA an unnecessary expense in the management of a clinically unstable shoulder?

Abstract: Background and purposeIn detection of glenoid labrum pathology, MR arthrography (MRA) has shown sensitivities of 88-100% and specificities of 89-93%. However, our practice suggested that there may be a higher frequency of falsely negative reports. We assessed the accuracy of this costly modality in practice.Patients and methodsWe retrospectively reviewed MRA reports of 90 consecutive patients with clinical shoulder instability who had undergone shoulder arthroscopy. All had a history of traumatic anterior shou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 15 publications
2
31
0
Order By: Relevance
“…This sensitivity of Bankart lesions is within the range previously reported in the literature (0.65-0.95) [21][22][23][24]. The 1.0 sensitivity of MRA for Hill-Sachs lesions was similar to that presented in the literature (0.96-1.0) [22,25]; however, the 0.8 specificity is lower than that previously reported [22,25].…”
Section: Discussionsupporting
confidence: 84%
“…This sensitivity of Bankart lesions is within the range previously reported in the literature (0.65-0.95) [21][22][23][24]. The 1.0 sensitivity of MRA for Hill-Sachs lesions was similar to that presented in the literature (0.96-1.0) [22,25]; however, the 0.8 specificity is lower than that previously reported [22,25].…”
Section: Discussionsupporting
confidence: 84%
“…Therefore, accurate identification of labral and glenohumeral ligament tears has become a significant diagnostic goal [20, 21]. The purpose of our study was to assess the diagnostic performance of MR arthrography in the diagnosis of anteroinferior labrum lesions, using arthroscopy as the reference standard and to classify these lesions.…”
Section: Discussionmentioning
confidence: 99%
“…MRI may also be augmented with the use of contrast, as in magnetic resonance arthrogram (MRA). Studies have reported good sensitivities and specificities with these two modalities (6)(7)(8). Some studies have gone further to show the superiority of MRA over MRI in the diagnosis of labral tears (5,8,9).…”
Section: Introductionmentioning
confidence: 99%